Sureśvara's contribution to Advaita - Markandeya Sastri, C., 1926- (Sundari Samskrita Vidyalaya ; copies can be had from C. Durgakumari, 1974)
On the life and work of Sureshvaracharya, disciple of Shankaracharya, founder of the school of Hindu Advaita (non-dualistic) Vedanta philosophy.